Physical Characterization of Carrageenan from Eucheuma cottonii and Alginate from Turbinaria ornata - Satrio Eko Nugroho; Dedin Finatsiyatul Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Seaweeds are valuable marine bioresources containing natural hydrocolloids widely used in the food, pharmaceutical, cosmetic, and biomaterial industries. This study investigated the extraction and physical characteristics of carrageenan from Eucheuma cottonii and alginate from Turbinaria ornata. Carrageenan was extracted using hot alkaline extraction, while alginate was obtained through acid treatment, alkaline conversion, and precipitation. The evaluated parameters included extraction yield, total soluble solids (TSS), and viscosity. Carrageenan showed a higher extraction yield (24.53%) than alginate (21.12%), whereas alginate exhibited higher TSS (12.00 °Brix) and viscosity (114.25 cP) than carrageenan (8.25 °Brix and 76.75 cP). The higher carrageenan yield was attributed to its simpler alkaline extraction process, while the greater TSS and viscosity of alginate were associated with soluble sodium alginate, residual minerals, and carboxyl groups that enhance water-binding capacity. These findings demonstrate the distinct physical properties of carrageenan and alginate, highlighting their different functional potentials as natural hydrocolloids. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption And ProductionSDG 14: Life Below Water